Preparation, characterization, and application of palm carotene microcapsule coated by rice protein isolate flaxseed gum complex - Choy, Hew Weng (2023)
Natural proteins, including plant-based proteins and their complexes with polysaccharides, have received limited attention in terms of their functional properties for food applications. In contrast, carotene has garnered significant interest from consumers and the food industry due to its health-promoting effects. However, the poor solubility of carotene poses substantial challenges for its inclusion in food formulations, particularly in aqueous-based systems. This study aimed to develop a stable palm carotene-based emulsion using a natural-based rice protein isolate-flaxseed gum (RPIFG) complex, followed by microencapsulation and subsequent incorporation into ice cream. In the first phase, various ratios of RPI-FG (ranging from 3:1 to 11:1) were employed to form complexes, which were then incorporated into the emulsion. The emulsion created using a 7:1 ratio of RPI-FG complex exhibited superior functionality. It featured the smallest droplet size (3.37 μm), a span index of 1.74, a viscosity of 8.48 mPa·s, and a creaming index (CI) of 26.67%. These values fell within an intermediate range compared to the other ratios on the 7th day of storage. Moving to the second phase, the formation of carotene microcapsules was accomplished using the emulsion produced with a 7:1 ratio of RPI-FG complex via spray drying. Various combinations of wall materials and core-to-wall material ratios were explored to create the microcapsules. Microcapsules produced with a combination of maltodextrin and starch sodium octenyl succinate (OSS) as the wall material, maintaining a 1:4 core-to-wall material ratio, displayed enhanced stability. They exhibited the highest microencapsulation efficiency (MEE) at 70.50%, significant carotene content (α-60.85% and β-72.79%), impressive water solubility index (79.60%), and a smooth surface as observed through scanning electron microscopy. Additionally, these microcapsules had the lowest moisture content (2.19%), a low water activity of 0.20, minimal water adsorption index of 0.50%, fair flow properties, and intermediate cohesiveness. In the third phase, the study delved into the storage stability, release characteristics, and in-vitro digestibility of the microencapsulated carotene emulsion, stabilized with a combination of maltodextrin and OSS as the wall material, maintaining a 1:4 core-to-wall material ratio. Over a rigorous 13-week storage period, minimal changes were observed in terms of MEE, carotene degradation, and peroxide value. In contrast, color changes increased, and chroma values decreased throughout the storage. Remarkably, these microcapsules displayed stability against varying ionic strengths. Most significantly, their bioaccessibility and the percentage of carotene release during in-vitro digestion were significantly higher compared to bulk oil. Finally, in the fourth phase, ice cream was fortified with these carotene microcapsules, and assessments of storage stability and sensory evaluations were conducted. Although there were slight differences in overrun and melting rate between ice cream variants with and without carotene microcapsules, the former exhibited a more vibrant color profile. However, carotene degradation occurred over a 4-week storage period, accompanied by an increase in firmness throughout storage. Sensory analysis results indicated moderate satisfaction among panelists, with a preference for ice cream containing carotene microcapsules. This confirmed the feasibility of incorporating carotene into ice cream to enhance its color, flavor, and nutritional value. In conclusion, this study underscores the potential of using plant-based proteins complexed with polysaccharides as a viable alternative to animal-derived emulsifiers. Furthermore, it highlights carotene's versatility in various food products, facilitated by the meticulous microencapsulation process using maltodextrin and OSS at a 1:4 core-to-wall ratio, resulting in impressive stability and microencapsulation efficiency exceeding 70%. This study highlights the promising potential of natural-based protein-polysaccharide complexes and microencapsulation techniques to enhance the incorporation of carotene into a range of food products, offering both functional benefits and improved consumer appeal.